The Impact of E-WOM and Digital Marketing on Unida Gontor Female Students' Wardah Product Purchase Decisions - Nusa Dewa Harsoyo; Hasna Dini Nur Fuady; Rusyda Afifah Ahmad; Soritua Ahmad Ramdani Harahap (TIJAB (The International Journal of Applied Business), 2026)
Background: This research aims to determine the influence of digital marketing and E-WOM on the purchase decisions of Wardah Unida Gontor students regarding products. Objective: This research examines the influence of digital marketing and E-WOM on the purchase decisions of Unida Gontor students regarding Wardah products. This study was analyzed with SmartPLS version 4.0.9.0. Method: This study employed a quantitative research design. Data were gathered through purposive sampling, yielding 112 respondents among Unida Gontor female students who had purchased Wardah products. Analysis was carried out using the SEM-PLS method. Results: Findings indicate that digital marketing does not significantly affect Wardah product purchase decisions, while E-WOM shows a positive and significant influence on those decisions. Conclusion: Contains Digital marketing had no significant effect on the purchase decisions of Unida Gontor female students. By contrast, E-WOM exerts a positive and meaningful influence on their decision to buy Wardah products. Keywords: Digital Marketing; Purchase Decision; Electronic Word of Mouth; Islamic Business Ethics.